Social media content optimization assistance for the community of Tanah Abang Traders Association ‘HIPTA’ - Dida Nurhaida; Ida Busnetty; Rinaldi Rustam; Fitri Nurhasna Amalia; Angga Prasetya (Universitas Muhammadiyah Magelang, 2023)
The purpose of this community service activity is to overcome the problems that are being faced by traders in Tanah Abang regional market, where their turnover dropping drastically during pandemic. The solution offered to solve this problem is by selling on the digital market through social media such as Instagram and Facebook. However, due to their lack of knowledge about digital marketing, learning is needed so that they can use the features that exist in social media applications, including creating marketing content. The activity was carried out by involving one of the communities, namely Tanah Abang Traders Association (HIPTA). The method implementing the activities carried out with a community development model approach is provided in the form of assistance. The results of the activity show that this assistance can be received by participants effectively and participants are being ready to adapt to the digital market.